A hybrid technique for facial feature detection - Ince, Erhan A.; Kaymak, S.; Çelik, Turgay (My University, 2005)
In this paper, we propose a facial feature detection technique which uses combination of image intensity, color, and geometrical features of faces and provide a performance analysis of the technique proposed. The paper provides a cost factors analysis for optimizing the correct detection of facial features. In addition it also introduces the idea of herustically setting the mouth location on occasions the proposed algorithm fails. The main novelty lies in the cost factor analysis and the herustic approach for locating the mouth. © 2005 IEEE.
Yüzsel öznitelik sezimi için karma bir teknik
IEEE 13th Signal Processing and Communications Applications Conference, SIU 2005 --
Keywords: Cost factor analysis; Facial feature detection technique; Geometrical features; Algorithms; Feature extraction; Image analysis; Optimization; Face recognition